Westerly upper air troughs and development of western disturbances over India - SINGH , M. S. (MAUSAM, 1979)
The characeteristics of a developing mid-tropospheric westerly trough over Indo-Pakistan area in wreter season have been studied with a view to investigate its relation with western disturbances which developed and affected north andcemral lnd ia during that penod.1I was found thatbothwereintimately connected. Light has been thrown on some othercharacteristic features of thewestern disturbances over the Indo-Pakistan region.